ORGANIZATIONAL AND ECONOMIC MECHANISM OF THE DEVELOPMENT OF RURAL AREAS - KOZAK, MYROSLAV (Herald of Khmelnytskyi National University. Economic sciences, 2021)
Rural development involves improving the quality of life and economic well-being of people living in rural areas, often relatively isolated and sparsely populated. Rural development has traditionally focused on the exploitation of natural resources, such as agriculture and forestry. However, rural areas have changed as a result of changes in global production networks and urbanization. Resource extraction and agriculture are increasingly being replaced as dominant economic engines by tourism, niche producers and recreation. The need for rural communities to view development from a broader perspective has led to a greater focus on a wide range of development goals rather than simply promoting agricultural or resource businesses. Education, entrepreneurship, physical and social infrastructure are crucial for the development of rural areas. Rural development is also characterized by an emphasis on local economic strategies. Unlike urban areas, which have a lot in common, rural areas are very different from each other, so there are many different approaches to rural development around the world. Comprehensive development of rural areas is formed due to a balanced combination of the potential of the rural area and a set of (internal and external) factors that ensure its development. It was determined that the integrated development of rural areas is a system of mutually determined, interconnected and interacting potential of this area and factors that ensure the efficiency and progressiveness of the development of rural areas both in the current conditions and in the future. The emerging crisis phenomena indicate a decrease in the solvency of the population, an increase in the threat to food security, and a deterioration in the living conditions of the peasants. Modern rural areas are faced with the search for a new ideological base, the conceptual provisions of which would allow, using the internal resources of the area, to diversify the economy and improve the quality parameters of the functioning of rural-type municipal entities. as peculiar the "driver" of their development.